A Study Of Luxury Fashion Brand Equity - Tong, Yew Wai (2008)
The purpose of this research is to established a luxury branding model for the prestige fashion manufacturers/marketers and prestige retail sectors and provide direction for prestige fashion industry and academic researchers in better understanding viable strategies to thi skey element of success in today's aggressive marketplace.